Immunogenicity of ChAdOx1 nCoV-19 Booster Vaccination Following Two CoronaVac Shots in Healthcare Workers - Wisit Prasithsirikul; Krit Pongpirul; Tanawin Nopsopon; Phanupong Phutrakool; Wannarat Pongpirul; Chatpol Samuthpongtorn; Pawita Suwanwattana; Anan Jongkaewwattana (Vaccines, 2022)
During the early phase of the COVID-19 pandemic, several countries, including Thailand, provided two shots of CoronaVac to healthcare workers. Whereas ChAdOx1 nCoV-19 is the promising vaccine as the booster dose, the data on immunogenicity when administered after CoronaVac have been limited. The purpose of this study was to evaluate the immunogenicity of ChAdOx1 nCoV-19 as the third dose vaccine in healthcare workers who previously received two shots of CoronaVac. The blood samples were obtained before the third vaccination dose, and one month and three months after vaccination. All participants were measured for humoral immunity including anti-spike IgG and neutralizing antibody by ELISA. Twenty participants were stratified by random samples based on baseline IgG status for a cellular immunity function test at three-month post-vaccination, which included T cell and B cell functions by ELISpot. This study showed significant improvement for both humoral and cellular immunity one month after vaccination. Subgroup analysis indicated a significantly higher neutralizing antibody improvement for the population with a negative anti-spike IgG at baseline. Our study suggests that, while immunity level declines at three months post-vaccination, the level was sufficiently high to protect against SARS-CoV-2.